2016
DOI: 10.1002/cpdd.254
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Single‐Dose, Double‐Blind, Placebo‐Controlled Safety Study of Noribogaine in Opioid‐Dependent Patients

Abstract: Ibogaine is a psychoactive substance that may reduce opioid withdrawal symptoms. This was the first clinical trial of noribogaine, ibogaine's active metabolite, in patients established on methadone opioid substitution therapy (OST). In this randomized, double-blind, placebo-controlled single ascending-dose study, we evaluated the safety, tolerability, and pharmacokinetics of noribogaine in 27 patients seeking to discontinue methadone OST who had been switched to morphine during the previous week. Noribogaine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 13 publications
(40 reference statements)
2
31
0
Order By: Relevance
“…Finally, noribogaine restored trafficking of hDAT-V158F from the neuronal soma to the axonal territories, thus providing independent evidence for its pharmacochaperoning activity. The therapeutic implications of our findings are self-evident; phase I trials show that noribogaine is reasonably well tolerated up to doses of 180 mg/day by adults ( 38 , 39 ). A trial of noribogaine may be justified in children suffering infantile dystonia and parkinsonism, which is due to the mutations hDAT-V158F and hDAT-G327R.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, noribogaine restored trafficking of hDAT-V158F from the neuronal soma to the axonal territories, thus providing independent evidence for its pharmacochaperoning activity. The therapeutic implications of our findings are self-evident; phase I trials show that noribogaine is reasonably well tolerated up to doses of 180 mg/day by adults ( 38 , 39 ). A trial of noribogaine may be justified in children suffering infantile dystonia and parkinsonism, which is due to the mutations hDAT-V158F and hDAT-G327R.…”
Section: Discussionmentioning
confidence: 73%
“…During the early period of exploration, ibogaine was mostly known for its ability to inspire a sense of wellbeing both mentally and physically. Ibogaine has also been used for the treatment of substance abuse because it interrupts drug addiction, relieves withdrawal symptoms, and significantly decreases the desire for cocaine, heroin, alcohol, and most other mind-altering drugs [ 1 4 ]. The pharmacology of ibogaine is quite complex and affects many different neurotransmitter systems simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In 1993–1994, The National Institute on Drug Abuse (NIDA) developed a Phase I investigation to evaluate pharmacokinetic and safety data in a fixed dosage study for cocaine dependence, but they decided not to fund the implementation of the protocol ( Alper, 2001 ; Alper et al, 2001 ). In two Phase I studies, low doses of noribogaine (the active metabolite of ibogaine, which has a distinct pharmacological profile) was well tolerated ( Glue et al, 2015 ) and showed a trend toward reduction in opioid withdrawal ratings ( Glue et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%